Ternary positive electrode material precursor particles, preparation method thereof, ternary positive electrode material and battery
Patent Information
- Application Number
- CN202610903414.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-22
- Publication Date
- 2026-10-13
AI Technical Summary
在这个背景下,由镍钴锰层状氧化物常被用于锂离子电池中的正极材料,虽然高镍正极材料有效提升了电池的能量密度,但是高镍正极存在的较差的循环性能和循环过程中严重的性能衰退问题制约了其发展应用
[0023]本发明的附加方面和优点将在下面的描述中部分给出,部分将从下面的描述中变得明显,或通过本发明的实践了解到。
Smart Images

Figure CN122897449A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, specifically to ternary cathode material precursor particles and their preparation methods, ternary cathode materials, and batteries. Background Technology
[0002] With the continued booming development of the new energy vehicle industry, the performance and cost requirements for lithium-ion batteries, the core component of new energy vehicles, are also rapidly increasing. Against this backdrop, nickel-cobalt-manganese layered oxides are commonly used as cathode materials in lithium-ion batteries. Although high-nickel cathode materials effectively improve the energy density of batteries, their poor cycle performance and severe performance degradation during cycling restrict their development and application.
[0003] Cathode precursors refer to compounds or mixtures used to prepare cathode materials for lithium-ion batteries, while ternary precursors specifically refer to precursor compounds composed of nickel, cobalt, and manganese. Currently, the most common method for synthesizing ternary precursors is co-precipitation, which allows for a synergistic effect among nickel, cobalt, and manganese, leveraging the advantages of all three elements. Studies have shown that high-nickel ternary precursors exhibit minimal structural changes after lithium mixing and high-temperature sintering, indicating that the structure of the ternary cathode material largely inherits the structure of the precursor, which is reflected in the battery's performance. Therefore, designing and optimizing the structure of ternary precursor materials (hereinafter referred to as precursors) plays a crucial role in improving the performance and stability of lithium-ion batteries. Summary of the Invention
[0004] Therefore, one object of the present invention is to provide a ternary cathode material precursor particle, which, when used to prepare a ternary cathode material, can effectively improve the performance of lithium-ion batteries.
[0005] In one aspect, the present invention provides a ternary cathode material precursor particle. According to an embodiment of the present invention, the ternary cathode material precursor particle is a secondary particle formed by the agglomeration of primary particles. The ternary cathode material precursor particle includes a core and an outer layer enclosing the core. The porosity of the core is greater than that of the outer layer, and the ratio of the diameter of the core to the particle size D50 of the secondary particle is 0.1 to 1. Therefore, the structure and size of the ternary cathode material particles prepared from the precursor particles are basically the same as those of the precursor particles, and the porosity distribution is also the same. That is, the ternary cathode material particles prepared from the precursor particles also include a core and an outer layer, with the porosity of the core being greater than that of the outer layer. Furthermore, the ratio of the diameter of the core to the particle size D50 of the ternary cathode material particles is also approximately 0.1 to 1. Thus, the combination of the aforementioned dimensions and porosity distribution can effectively reduce the internal resistance of the ternary cathode material during long-cycle operation, and can also facilitate the rapid penetration and diffusion of the electrolyte into the particle interior, thereby contributing to the improvement of battery cycle life and rate capability.
[0006] According to an embodiment of the present invention, the ratio of the porosity of the core to the porosity of the outer layer is 1.5 to 4, and / or the ratio of the diameter of the core to the particle size D50 of the secondary particles is 0.1 to 0.75.
[0007] According to an embodiment of the present invention, the porosity of the core is greater than 7%, preferably, the porosity of the core is 7% to 30%; and / or, the maximum porosity of the outer layer is ≤7%.
[0008] According to an embodiment of the present invention, the porosity of the outer layer near the core is greater than the porosity of the outer layer away from the core.
[0009] According to an embodiment of the present invention, the outer layer includes at least two sub-outer layers along the direction from the outside to the inside, and the porosity of the sub-outer layers gradually decreases in the direction away from the core; preferably, in the direction away from the core, the outer layer includes a first sub-outer layer and a second sub-outer layer arranged sequentially.
[0010] According to an embodiment of the present invention, the outer layer satisfies at least one of the following conditions: the porosity of the first sub-outer layer is 2% to 4%; the porosity of the second sub-outer layer is 1.1% to 2.2%; the ratio of the thickness of the first sub-outer layer and the second sub-outer layer to the diameter of the secondary particles is 0.005 to 0.25, respectively; and the thickness of the first sub-outer layer and the second sub-outer layer is independently 0.3 to 1.5 μm.
[0011] According to an embodiment of the present invention, the diameter of the core is 1 to 10 micrometers, and / or the particle size D50 of the secondary particles is 6 to 30 μm.
[0012] According to an embodiment of the present invention, the secondary particles satisfy at least one of the following conditions: the tap density of the secondary particles is 1.85~2.15 g / cm³. 3 The sphericity of the secondary particles is 0.65~0.99; the specific surface area of the secondary particles is 3~30 m². 2 / g; In the XRD test of the secondary particles, the peak intensity ratio I(001) / I(101) of the characteristic peak of the (001) crystal plane and the characteristic peak of the (101) crystal plane is 0.7~1.2; The particle size distribution K90 of the secondary particles is 0.25~0.85, where K90=(D90-D10) / D50.
[0013] According to an embodiment of the present invention, the primary particles satisfy at least one of the following conditions: the primary particles of the outer layer are arranged radially in a direction away from the core; the morphology of the primary particles includes at least one of sheet-like, rod-like, and block-like shapes, wherein, optionally, the average thickness of the sheet-like primary particles is 5~200 nm, preferably 80~170 nm; optionally, the average length of the sheet-like primary particles is 200~450 nm; optionally, the aspect ratio of the rod-like primary particles is 20~200.
[0014] In another aspect of the present invention, the present invention provides a method for preparing the aforementioned ternary cathode material precursor particles. According to an embodiment of the present invention, the method for preparing ternary cathode material precursor particles includes: mixing a precipitant and a complexing agent in a reaction vessel to prepare a base solution; in a first reaction stage, continuously adding the precipitant, the complexing agent, and the metal salt solution to the base solution to obtain a first-stage mixture and form the core of the ternary cathode material precursor particles, and then proceeding to a second reaction stage; in the second reaction stage, continuously adding the precipitant, the complexing agent, and the metal salt solution to the first-stage mixture to obtain the ternary cathode material precursor particles, wherein the addition flow rates of the precipitant, the complexing agent, and the metal salt solution in the first reaction stage are all less than the addition flow rates of the precipitant, the complexing agent, and the metal salt solution in the second reaction stage, and the pH value of the first reaction stage is greater than or equal to the pH value of the second reaction stage, and the stirring speed of the first reaction stage is greater than the stirring speed of the second reaction stage. Therefore, the above preparation method can effectively prepare ternary cathode material precursor particles with the above structure, which can release the anisotropic stress accumulated in the core region during the growth of the outer structure, avoid stress concentration inside the secondary particles, and alleviate local cracking. Moreover, the process is simple, easy to implement, easy to control and manage and mass-produce, and has high production efficiency.
[0015] According to an embodiment of the present invention, in the first reaction stage, the flow rate A1 of the metal salt solution, the flow rate B1 of the complexing agent, and the flow rate C1 of the precipitant remain unchanged, and the concentration D1, pH value E1, and stirring speed F1 of the complexing agent remain unchanged.
[0016] According to an embodiment of the present invention, the second reaction stage satisfies at least one of the following conditions: the flow rate of the added metal salt solution gradually increases from A1 to A2 within a first predetermined time and then remains constant; the flow rate of the added complexing agent gradually increases from B1 to B2 within the first predetermined time and remains constant at B2 within a second predetermined time, then gradually decreases from B2 to B3 within a third predetermined time and remains constant, with B2>B3>B1; the flow rate of the added precipitant gradually increases from C1 to C2 within the first predetermined time and remains constant at C2 within the second predetermined time, then gradually decreases from C2 to C3 within the third predetermined time and remains constant, with C2>C3>C1; the concentration of the complexing agent gradually increases from D1 within the first predetermined time. The pH value is gradually reduced from E1 to E2 within the first predetermined time, and remains unchanged at E2 within the second predetermined time. Then, E2 gradually decreases to E3 within the third predetermined time and remains unchanged. Alternatively, the pH value remains unchanged at E1 within the fourth predetermined time, and then gradually decreases to E2 and remains unchanged. The stirring speed is gradually reduced from F1 to F2, maintained at F2 for a certain time, gradually reduced from F2 to F3, maintained at F3 for a certain time, gradually reduced from F3 to F4, ..., gradually reduced from Fn-1 to Fn and remains unchanged, where n is an integer greater than or equal to 3.
[0017] According to an embodiment of the present invention, the second reaction stage satisfies at least one of the following conditions: A1 is 3~12 L / h, A2 is 18~35 L / h, and the flow rate is uniformly increased at 1~2.5 L / h during the gradual increase from A1 to A2; B1 is 0.5~6 L / h, B2 is 3~10 L / h, B3 is 2~9 L / h, and the flow rate is uniformly increased at 0.1~0.6 L / h during the gradual increase from B1 to B2, and uniformly decreased at 0.1~0.6 L / h during the gradual decrease from B2 to B3; C1 is 3.5~12 L / h, C2 is 10~20 L / h, C3 is 6~18 L / h, and the flow rate is uniformly increased at 0.5~1.5 L / h during the gradual increase from C1 to C2. During the process of gradually decreasing C2 to C3, the flow rate is uniformly decreased at a rate of 0.2~0.8 L / h; D1 is 0.5~6 g / L, D2 is 1.5~6 g / L, and D3 is 1~5 g / L. During the process of gradually increasing D1 to D2, the flow rate is uniformly increased at a rate of 0.05~0.3 g / L·h, and during the process of gradually decreasing D2 to D3, the flow rate is uniformly decreased at a rate of 0.1~0.8 g / L·h; E1 is 11.8~12.5, E2 is 11.2~12.0, and E3 is 10.3~11.2. The rate of change of the pH value is 0.002 / h~0.3 / h; F1 is 50~500 rpm, and the rate of decrease of the stirring speed is 5~15 rpm / h.
[0018] According to an embodiment of the present invention, the base liquid satisfies at least one of the following conditions: pH is 10.45~11.95; the concentration of the complexing agent is 7.0~12 g / L.
[0019] According to embodiments of the present invention, the preparation method further satisfies at least one of the following conditions: the concentration of the metal salt solution is 120-145 g / L, and during the coprecipitation reaction, the flow rate of the metal salt solution added is 1.0%-10.0% of the usable volume of the reaction vessel; the mass fraction of the complexing agent is 7-10 wt%, and during the coprecipitation reaction, the flow rate of the complexing agent added is 0.3%-3% of the usable volume of the reaction vessel; the concentration of the precipitant is 200-450 g / L, and during the coprecipitation reaction, the flow rate of the precipitant added is 1.5%-10% of the usable volume of the reaction vessel.
[0020] According to an embodiment of the present invention, the preparation method also satisfies at least one of the following conditions: the reaction temperature of the coprecipitation reaction is 50~90℃; the coprecipitation reaction is carried out in a low-oxygen atmosphere or an inert atmosphere, and the volume ratio of oxygen in the reaction atmosphere is ≤5%; the solid content in the coprecipitation reaction is 400-1000 g / L.
[0021] In another aspect, the present invention provides a ternary cathode material. According to an embodiment of the present invention, the ternary cathode material is prepared from a lithium source and the aforementioned ternary cathode material precursor particles. This ternary cathode material exhibits low internal impedance during long-cycle operation, and the electrolyte can rapidly penetrate and diffuse into the ternary cathode material particles, thereby contributing to improved battery cycle life and rate capability.
[0022] In another aspect, the present invention provides a battery. According to an embodiment of the present invention, the battery includes a positive electrode sheet, the positive electrode sheet including a positive current collector and a positive active film layer located on the surface of the positive current collector, the positive active film layer including the aforementioned ternary positive electrode material. Therefore, the battery has good cycle life, rate capability, and other battery performance.
[0023] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Attached Figure Description
[0024] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which: Figure 1 This is a schematic diagram of ternary cathode material precursor particles in one embodiment of the present invention.
[0025] Figure 2 This is a cross-sectional view of the ternary cathode material precursor particles in another embodiment of the present invention.
[0026] Figure 3 and Figure 4 This is a scanning electron microscope image of the ternary cathode material precursor particles in Example 1; Figure 5 and Figure 6 This is a scanning electron microscope image of the ternary cathode material precursor particles in Example 1; Figure 7 and Figure 8 This is a scanning electron microscope image of the ternary cathode material precursor particles in Comparative Example 1. Detailed Implementation
[0027] The present invention will be explained below with reference to embodiments. Those skilled in the art will understand that the following embodiments are for illustrative purposes only and should not be considered as limiting the scope of the invention. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0028] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0029] The present invention will now be described with reference to specific embodiments. It should be noted that these embodiments are merely descriptive and do not limit the present invention in any way.
[0030] The terms "first" and "second" used in this document are for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature marked "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this application, "multiple" means two or more, unless otherwise explicitly specified.
[0031] In one aspect of the invention, a ternary cathode material precursor particle is provided. According to an embodiment of the invention, referring to… Figure 1 and Figure 2 ( Figure 2(This is a cross-sectional view of the ternary cathode material precursor particles). The ternary cathode material precursor particles 100 are secondary particles formed by the agglomeration of primary particles 10. The ternary cathode material precursor particles 100 include a core 110 and an outer layer 120 that surrounds the core 110. The porosity of the core 110 is greater than that of the outer layer 120, and the ratio of the diameter of the core to the particle size D50 of the secondary particles is 0.1~1 (for example, the ratio is 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, etc.). Therefore, the structure and size of the ternary cathode material particles prepared from the precursor particles are basically the same as those of the precursor particles, and the porosity distribution is also the same. That is, the ternary cathode material particles prepared from the precursor particles also include a core and an outer layer, with the porosity of the core being greater than that of the outer layer. Moreover, the ratio of the diameter of the core to the particle size D50 of the ternary cathode material particles is also basically 0.1~1. Thus, this unique structure can not only avoid stress concentration inside the secondary particles and alleviate local cracking, but also effectively reduce the internal impedance of the ternary cathode material during long-cycle operation. Furthermore, the high porosity of the core can also facilitate the rapid penetration and diffusion of the electrolyte into the interior of the ternary cathode material particles, while buffering volume expansion and shortening the ion transport path. The low porosity of the outer layer can effectively ensure the stability of the ternary cathode material particle structure and energy density, thereby contributing to the improvement of battery cycle life and rate capability.
[0032] In some specific embodiments, the ratio of the core diameter to the secondary particle size D50 is 0.1 to 0.75. This can more effectively improve the electrochemical performance of the battery.
[0033] In some embodiments, the ratio of the porosity of the core to the porosity of the outer layer is 1.5 to 4, for example, ratios of 1.5, 1.6, 1.8, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.2, 3.5, 3.8, and 4. Therefore, compared to the core, the core of the precursor particles has a relatively high porosity, which can effectively avoid stress concentration within the secondary particles, alleviate local cracking, and effectively facilitate the rapid penetration and diffusion of the electrolyte into the ternary cathode material particles.
[0034] In some embodiments, the porosity of the core is greater than 7%, such as 7%, 8%, 9%, 10%, 12%, 14%, 15%, 18%, 20%, 22%, 24%, 25%, 26%, 28%, 30%, 32%, 34%, 35%, 36%, and 38%. This loose and porous core structure effectively promotes the rapid penetration and diffusion of the electrolyte into the particle interior, improving lithium-ion transport efficiency. In some specific embodiments, the core porosity is 7% to 30%, which further ensures the compactness of the precursor particles, improves the stability of the ternary cathode material, and helps to increase the energy density and battery rate.
[0035] In some embodiments, the maximum porosity of the outer layer is less than or equal to 7%, such as 7%, 6.5%, 6%, 5.5%, 5%, 4.5%, 4%, 3.5%, and 3%. The ternary cathode material prepared in this way has suitable porosity, effectively ensuring the compactness of the precursor particles and the ternary cathode material, improving the mechanical properties of the particles to prevent particle cracking, and also helping to improve the energy density of the ternary cathode material and increase the battery rate. The maximum porosity of the outer layer is the average value calculated from 200 randomly selected secondary particles.
[0036] In some embodiments of the present invention, the porosity is calculated as follows: the ratio of the sum of the pore areas of the selected regions on the maximum cross-sectional circle of the secondary particle to the total area of the selected regions. Specifically, the formula is: Porosity = Sum of pore areas within the selected regions ÷ Total area of the selected regions × 100%. The method for obtaining the maximum cross-sectional circle is as follows: The three-dimensional secondary particle is cross-sectioned or projected in two dimensions. Among all cross-sections or projections, the circumscribed circle corresponding to the contour with the largest circumscribed circle diameter is the maximum cross-sectional circle of that secondary particle. The selected regions are divided according to the diameter of the core or the thickness of the outer layer, etc. During electron microscopy scanning and identification, the contrast is 50% and the brightness is 20%. The porosity is obtained by calculating the average value of 200 randomly selected secondary particles.
[0037] In some embodiments, the porosity of the outer layer near the core is greater than that of the outer layer farther from the core; in other words, in the direction farther from the core, the porosity of the relatively outer side of the outer layer is less than that of the relatively inner side. Therefore, this variation in outer layer porosity can better prevent stress concentration within secondary particles, alleviate localized cracking, and better promote the rapid penetration and diffusion of the electrolyte into the particle interior, ensuring the stability of the particle structure and the material's good energy density.
[0038] In some embodiments, the outer layer comprises at least two sub-outer layers along the direction from the outside in (i.e., the direction closer to the core), and the porosity of the sub-outer layers gradually decreases in the direction away from the core. Thus, the outer layer of the above structure can better avoid stress concentration within secondary particles, alleviate local cracking, better promote the rapid penetration and diffusion of electrolyte into the particle interior, and ensure the stability of the particle structure and the material's good energy density.
[0039] In some specific embodiments, in the direction away from the core, the outer layer includes a first sub-outer layer and a second sub-outer layer arranged sequentially, such that the porosity of the first sub-outer layer is greater than that of the second sub-outer layer. Therefore, the outer layer of the above structure can better avoid stress concentration within the secondary particles, alleviate local cracking, and better promote the rapid penetration and diffusion of the electrolyte into the particle interior, ensuring the stability of the particle structure and the material's good energy density; moreover, it is easier to implement in the manufacturing process.
[0040] In some specific embodiments, the porosity of the first sub-outer layer is 2%~4% (e.g., 2%, 2.3%, 2.5%, 2.8%, 3.0%, 3.2%, 3.5%, 3.8%, 4%, etc.), and the porosity of the second sub-outer layer is 1.1%~2.2% (e.g., 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, etc.). The low porosity of the outer layer effectively ensures the stability of the ternary cathode material particle structure and its energy density, thereby contributing to improved battery cycle life and rate capability.
[0041] In some specific embodiments, the ratio of the thickness of the first sub-outer layer and the second sub-outer layer to the diameter of the secondary particle is 0.005 to 0.25, for example, the ratio of the thickness of the first sub-outer layer to the diameter of the secondary particle is 0.005 to 0.25 (e.g., 0.005, 0.01, 0.03, 0.05, 0.08, 0.1, 0.12, 0.15, 0.18, 0.2, 0.22, 0.25, etc.), and the ratio of the thickness of the first sub-outer layer to the diameter of the secondary particle is 0.005 to 0.25 (e.g., 0.005, 0.01, 0.03, 0.05, 0.08, 0.1, 0.12, 0.15, 0.18, 0.2, 0.22, 0.25, etc.). Therefore, the appropriate thickness ratio of the first sub-outer layer and the second sub-outer layer can ensure the better strength of the precursor particles of the ternary cathode material. The strong lattice constraint of the first sub-outer layer material results in good suppression of cyclic expansion of the ternary cathode material, making the particles less prone to cracking and the structure stable. The second sub-outer layer ensures a relatively low interface impedance, which helps to improve the rate performance and other properties of the ternary cathode material.
[0042] In some specific embodiments, the thickness of the first sub-outer layer and the second sub-outer layer are each independently 0.3–1.5 μm, for example, the thicknesses of the first and second sub-outer layers are 0.3 μm, 0.5 μm, 0.7 μm, 0.9 μm, 1.0 μm, 1.2 μm, 1.4 μm, and 1.5 μm, respectively. The thicknesses of the first and second sub-outer layers can be the same or different, as long as the above-mentioned ratio and thickness requirements are met.
[0043] In some embodiments, the diameter of the core is 1-10 micrometers, such as 1 micrometer, 1.5 micrometers, 2 micrometers, 2.5 micrometers, 3 micrometers, 3.5 micrometers, 4 micrometers, 4.5 micrometers, 5 micrometers, 6 micrometers, 7 micrometers, 8 micrometers, 9 micrometers, 10 micrometers, etc.; the particle size D50 of the secondary particles is 6-30 μm, such as 6 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm, 28 μm, 30 μm, etc. Precursor particles of the above sizes help improve the activity and capacity of the ternary cathode material, and can help improve cycle thermal stability and anti-gas strength, ensuring good wettability of the electrolyte to the cathode material. The diameter of the core refers to the average diameter of the core.
[0044] In some embodiments, the particle size distribution K90 of the secondary particles is 0.25~0.85, where K90 = (D90 - D10) / D50, and K90 represents the width of the particle size distribution; the larger K90 is, the wider the distribution. The particle size distribution K90 of the secondary particles in this invention indicates that they have a suitable compaction density, which is beneficial for improving the compaction density of the ternary cathode material, and thus beneficial for improving the electrochemical performance of the battery.
[0045] The above-mentioned "D50", also known as average particle size or median particle size, represents the particle size value corresponding to 50% of the cumulative particle size distribution curve, and can be regarded as the average particle size of the material; "D10" represents the particle size corresponding to 10% of the cumulative particle size distribution of a sample, which means that 10% of the particles are smaller than it; "D90" represents the particle size corresponding to 90% of the cumulative particle size distribution of a sample, which means that 90% of the particles are smaller than it. In some embodiments, the tap density of the secondary particles is 1.85~2.15 g / cm³. 3 The aforementioned tap density of the precursor secondary particles can enable the ternary cathode material prepared from them to have a better tap density, which is beneficial to improving the energy density and cycle life of the cathode. At the same time, it is also beneficial to obtain an electrode with suitable porosity, which in turn is beneficial to the full wetting of the electrolyte and the improvement of rate performance.
[0046] In some embodiments, the sphericity of the secondary particles is 0.65~0.99, for example, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, and 0.99. Thus, the secondary particles of the precursor have good sphericity, and the ternary cathode material prepared from them also has good sphericity. This higher sphericity results in better particle flowability, which in turn optimizes powder packing. In terms of process, this facilitates high-speed continuous coating, improves electrode consistency, and ensures uniform stress on the ternary material particles during electrode compaction, helping to increase the tap density of the electrode. This allows for a better balance of various battery performance characteristics, such as energy density, cycle life, and rate capability.
[0047] The formula for calculating the sphericity is: Sphericity γ = 4πS / L 2 Where S is the cross-sectional area passing through the geometric center of the secondary particle, and L is the perimeter of the cross-section.
[0048] In some embodiments, the specific surface area of the secondary particles is 3~30 m². 2 / g, for example, 3m 2 / g、5 m 2 / g、8 m 2 / g、10 m 2 / g、12 m 2 / g、15 m 2 / g、18 m 2 / g、20 m 2 / g、23 m 2 / g、25 m 2 / g、28 m 2 / g、30 m 2 / g etc. The precursor secondary particles have a suitable specific surface area, which helps to increase the contact area between the ternary cathode material and the electrolyte, shorten the diffusion path of lithium ions, and at the same time ensure the high energy density of the electrode and the structural stability of the particles.
[0049] In some embodiments, in the XRD test of the secondary particles, the peak intensity ratio I(001) / I(101) of the characteristic peak of the (001) crystal plane and the characteristic peak of the (101) crystal plane is 0.7~1.2, for example, I(001) / I(101) is 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, etc. The above peak intensity ratio indicates that the secondary particles have a suitable lithium-ion transition rate in the battery, which helps to improve battery performance.
[0050] In some embodiments, refer to Figure 2In the direction away from the core 110, the primary particles of the outer layer 120 are arranged radially, that is, the primary particles of the outer layer are arranged outward from the inside, and the outer layer has a distinct radial structure. Therefore, the outer layer with the above structure can further effectively avoid stress concentration inside the secondary particles, alleviate local cracking, further reduce the internal impedance of the ternary cathode material during long-cycle operation, and better facilitate the rapid penetration and diffusion of electrolyte into the particle interior, thus being more conducive to improving battery performance.
[0051] In some embodiments, the primary particle morphology includes at least one of flake, rod, and block shapes.
[0052] In some specific embodiments, the average thickness of the sheet-like primary particles is 5~200 nm (e.g., 5 nm, 10 nm, 50 nm, 80 nm, 100 nm, 120 nm, 150 nm, 180 nm, 200 nm, etc.), preferably 80~170 nm.
[0053] In some specific embodiments, the average length of the sheet-like primary particles is 200~450nm, such as 200nm, 230nm, 250nm, 280nm, 300nm, 320nm, 350nm, 380nm, 400nm, 420nm, 450nm, 480nm, 500nm, etc.
[0054] In some specific embodiments, the aspect ratio of the rod-shaped primary particles is 20 to 200, such as 20, 50, 80, 100, 120, 150, 180, 200, etc.
[0055] In some embodiments of the present invention, the ternary cathode material precursor particles are layered hydroxides with the general chemical formula Ni. x Co y M z T p (OH) 2-q Wherein, M is selected from one or more of Mn, Fe, Cr, Cu, Ti, Mg, W, Mo, Nb, Ca, Zn, Sn, Zr, and Al, and T is selected from one or more of F, P, B, and O, where 0≤x≤1, 0≤y≤1, 0≤z≤1, and 0≤p≤1, and the range of values for q is determined according to the principle of electroneutrality of chemical composition. Further, in some specific embodiments, 0.8≤x<1, 0≤y≤0.2, 0≤z≤0.2, and 0≤p≤0.5.
[0056] In another aspect, the present invention provides a method for preparing the aforementioned ternary cathode material precursor particles. According to an embodiment of the present invention, the method for preparing ternary cathode material precursor particles includes: S100: The precipitant and complexing agent are mixed in a reaction vessel to prepare the base liquid.
[0057] In some embodiments, the complexing agents in this invention are all ammonium ion donors, such as ammonia. In some embodiments, the mass fraction of the complexing agent is 7-10 wt%.
[0058] In some embodiments, the precipitant is a hydroxide solution of alkali metal ions, such as a sodium hydroxide solution or a potassium hydroxide solution. In some embodiments, the concentration of hydroxide in the precipitant is 200~450 g / L.
[0059] In some embodiments, the concentration of the complexing agent in the substrate is 7.0~12 g / L.
[0060] In some embodiments, the pH of the substrate is 10.45 to 11.95, such as 10.45, 10.5, 10.6, 10.7, 10.8, 10.9, 11.0, 11.1, 11.2, 11.3, 11.4, 11.5, 11.6, 11.7, 11.8, 11.9, 11.95, etc. Therefore, the substrate with the above pH values can provide a good reaction environment for the subsequent co-precipitation reaction and improve the reaction efficiency.
[0061] S200: In the first reaction stage, precipitant, complexing agent and metal salt solution are continuously added to the base liquid to obtain the first stage mixture and form the core of the ternary cathode material precursor particles, and then enter the second reaction stage.
[0062] S300: In the second reaction stage, precipitant, complexing agent and metal salt solution are continuously added to the mixture of the first stage to obtain ternary cathode material precursor particles. The addition flow rates of the precipitant, complexing agent and metal salt solution in the first reaction stage are all less than the addition flow rates of the precipitant, complexing agent and metal salt solution in the second reaction stage, and the pH value of the first reaction stage is greater than or equal to the pH value of the second reaction stage. The stirring speed of the first reaction stage is greater than the stirring speed of the second reaction stage.
[0063] According to an embodiment of the present invention, the first reaction stage and the second reaction stage in the above preparation method constitute a co-precipitation reaction process. The first reaction stage is used to form the core of the ternary cathode material precursor particles, and the second reaction stage is used to form the outer layer of the ternary cathode material precursor particles. The ternary cathode material precursor particles with the above structure can release the anisotropic stress accumulated in the core region during the growth of the outer layer structure, avoid stress concentration inside the secondary particles, and alleviate local cracking. It can also reduce the internal impedance of the ternary cathode material during long-cycle operation. Moreover, the high porosity of the core can also help the electrolyte to quickly penetrate and diffuse into the interior of the ternary cathode material particles, while buffering the volume expansion and shortening the ion transport path. The low porosity of the outer layer can effectively ensure the stability of the ternary cathode material particle structure and the energy density, thereby contributing to the improvement of battery cycle and rate. In addition, the process is simple, easy to implement, easy to control and manage and mass-produce, and has high production efficiency.
[0064] In some embodiments, the metal salt solution includes soluble salts of nickel, cobalt, and manganese, such as at least one of nitrates, chlorides, and / or sulfates of nickel, cobalt, and manganese.
[0065] In some embodiments, the concentration of the metal salt solution is 120~145 g / L, such as 120 g / L, 125 g / L, 130 g / L, 135 g / L, 140 g / L, 145 g / L, etc. This concentration is the total concentration of all metal salts, and the ratio of each metal salt can be calculated by those skilled in the art based on the molar ratio of each metal element in the target ternary cathode material.
[0066] In some embodiments, during the co-precipitation reaction (i.e., including a first reaction stage and a second reaction stage), the flow rate of the added metal salt solution is 1.0% to 10.0% of the available volume of the reaction vessel, for example, 1.0%, 2.0%, 3.0%, 4.0%, 5.0%, 6.0%, 7.0%, 8.0%, 9.0%, 10.0%, etc. This ensures the smooth progress of the reaction and prevents the solution in the reaction vessel from becoming too large in volume during the later stages of the reaction, which could lead to uneven mixing or splashing, thus affecting the product yield.
[0067] In some embodiments, during the coprecipitation reaction, the flow rate of the complexing agent added is 0.3% to 3% of the available volume of the reaction vessel, such as 0.3%, 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, 2.2%, 2.5%, 2.8%, 3.0%, etc. This ensures the smooth progress of the reaction and prevents the solution in the reaction vessel from becoming too large in volume during the later stages of the reaction, which could lead to uneven mixing or splashing, thus affecting the product yield.
[0068] In some embodiments, during the co-precipitation reaction, the flow rate of the precipitant added is 1.5% to 10% of the available volume of the reaction vessel, for example, 1.5%, 2.0%, 3.0%, 4.0%, 5.0%, 6.0%, 7.0%, 8.0%, 9.0%, 10.0%, etc. This ensures the smooth progress of the reaction and prevents the solution in the reaction vessel from becoming too large in volume during the later stages of the reaction, which could lead to uneven mixing or splashing, thus affecting the product yield.
[0069] In some embodiments, during the first reaction stage, the flow rates A1 of the metal salt solution, B1 of the complexing agent, and C1 of the precipitant remain constant, as do the concentration D1 of the complexing agent, the pH value E1, and the stirring speed F1. This stable flow rate of each raw material contributes to the formation of a relatively homogeneous and stable core structure.
[0070] In some embodiments, the duration of the first reaction stage can be flexibly set by those skilled in the art based on actual conditions such as the radius of the desired core, the flow rate and concentration of each raw material, and no limitation is imposed here. In some specific embodiments, the duration of the first reaction stage can be 1.5 to 8 hours.
[0071] For the second reaction stage, the required flow rates of each raw material, stirring speed, and pH changes of the mixed solution are as follows: In some embodiments, the flow rate of the metal salt solution is gradually increased from A1 to A2 within a first predetermined time and then remains constant. That is, after entering the second reaction stage, the flow rate of the metal salt solution is gradually increased from A1 to A2 and then maintained at the flow rate of A2 to continue the reaction. In some specific embodiments, A1 is 3~16 L / h and A2 is 18~35 L / h. During the process of gradually increasing from A1 to A2, the flow rate of the metal salt solution is increased uniformly at a flow rate of 1~3.5 L / h per hour.
[0072] In some embodiments, the flow rate of the complexing agent is gradually increased from B1 to B2 within a first predetermined time (i.e., after entering the second reaction stage, the flow rate of the complexing agent is gradually increased from B1 to B2), and then kept constant at B2 within a second predetermined time. Then, B2 is gradually decreased to B3 within a third predetermined time, and the flow rate of the complexing agent remains constant at B3, with B2>B3>B1. In some specific embodiments, B1 is 0.5~10 L / h, B2 is 3~20 L / h, and B3 is 2~15 L / h. During the process of gradually increasing the flow rate of the complexing agent from B1 to B2, the flow rate is increased uniformly at a rate of 0.1~1.2 L / h per hour. During the process of gradually decreasing the flow rate of the complexing agent from B2 to B3, the flow rate is decreased uniformly at a rate of 0.1~1.5 L / h per hour.
[0073] In some embodiments, the concentration of the complexing agent is gradually increased from D1 to D2 within a first predetermined time period (i.e., after entering the second reaction stage, the concentration of the complexing agent is gradually increased from D1 to D2), and then kept constant at D2 within a second predetermined time period. Then, the concentration of the complexing agent is gradually decreased from D2 to D3 within a third predetermined time period, and the concentration of the complexing agent is kept constant at D3, with D2>D3>D1. In some specific embodiments, D1 is 0.5~10 g / L, D2 is 1.5~15 g / L, and D3 is 1~12 g / L. During the process of gradually increasing the concentration of the complexing agent from D1 to D2, the concentration of the complexing agent is increased uniformly at a flow rate of 0.05~0.3 g / L·h. During the process of gradually decreasing the concentration of the complexing agent from D2 to D3, the concentration of the complexing agent is decreased uniformly at a flow rate of 0.1~0.8 g / L·h.
[0074] In some embodiments, the precipitant flow rate is gradually increased from C1 to C2 within a first predetermined time (i.e., after entering the second reaction stage, the precipitant flow rate is gradually increased from C1 to C2), and the precipitant flow rate C2 is kept constant within a second predetermined time. Then, the precipitant flow rate is gradually decreased from C2 to C3 within a third predetermined time and remains constant, with C2>C3>C1. In some specific embodiments, C1 is 3.5~15L / h, C2 is 10~25L / h, and C3 is 6~20L / h. During the process of gradually increasing the precipitant flow rate from C1 to C2, the precipitant flow rate is increased uniformly at a flow rate of 0.5~2.5L / h. During the process of gradually decreasing the precipitant flow rate from C2 to C3, the precipitant flow rate is decreased uniformly at a flow rate of 0.2~1L / h.
[0075] The pH value changes can follow several patterns, as detailed below: In some embodiments, the pH value gradually decreases from E1 to E2 within a first predetermined time (i.e., after entering the second reaction stage, the pH value gradually decreases from E1 to E2), and remains constant at E2 within a second predetermined time. Then, the pH value gradually decreases from E2 to E3 within a third predetermined time, and remains constant at E3. In other embodiments, the pH value remains constant at E1 within a fourth predetermined time (i.e., within the fourth predetermined time after the second reaction stage begins from the first reaction stage), and then gradually decreases from E1 to E2 and remains constant. In some specific embodiments, E1 is 11.8~12.5, E2 is 11.2~12.0, and E3 is 10.3~11.2. During the pH decrease process, the rate of pH change is 0.002 / h~0.3 / h. The pH values mentioned above are at 45°C.
[0076] In some embodiments, after entering the second reaction stage, the stirring speed gradually decreases from F1 to F2, is maintained at F2 for a certain period of time, then gradually decreases from F2 to F3, is maintained at F3 for a certain period of time, then gradually decreases from F3 to F4, and so on, gradually decreasing from Fn-1 to Fn and then remaining constant, where n is an integer greater than or equal to 3. In some specific embodiments, F1 is 50~500 rpm, and the rate of decrease in stirring speed during the change of stirring speed is 5~15 rpm / h. For example, in a coprecipitation reaction, during the first stage of the reaction, the stirring speed is M (F1) for the first 0-3 hours of synthesis. From the 3rd to the 5th hour, the stirring speed is uniformly reduced to M-20 (F2) at a rate of 10 rpm / h for 2 hours. From the 5th to the 8th hour, the stirring speed remains at M-20. From the 8th to the 10th hour, the stirring speed is uniformly reduced to M-40 (F3) at a rate of 10 rpm / h for 2 hours. From the 10th to the 13th hour, the stirring speed is M-40. From the 13th to the 15th hour, the stirring speed is uniformly reduced to M-60 (F4) at a rate of 10 rpm / h for 2 hours. From the 15th to the 18th hour, the stirring speed is M-60. Then, from the 18th to the 20th hour, the stirring speed is uniformly reduced to M-76 (F5) at a rate of 8 rpm / h for 2 hours. From the 20th to the 23rd hour, the stirring speed is M-76. Finally, from the 23rd to the 25th hour, the stirring speed is uniformly reduced to M-76 at a rate of 8 rpm / h for 2 hours. The stirring speed was reduced at a constant rate of M-92 (F6) from 25 to 27 h, and then the stirring speed was reduced to M-92 after 27 h.
[0077] According to an embodiment of the present invention, in the above method for preparing ternary cathode material precursor particles, each parameter changes gradually at a certain rate. This ensures the controllable reaction conditions of the core and outer layer, and avoids excessive fluctuations in parameters such as the concentration and pH value of each material during the outer layer growth process. Excessive fluctuations may cause side reactions such as secondary particle agglomeration and material recrystallization. When the average particle size D50 of the precursor secondary particles grows to the target particle size, the feeding is stopped, and an alkaline solution of the target reaction product is obtained. The generated secondary particles can have the same morphology as the primary particles.
[0078] According to some embodiments of the present invention, the reaction temperature of the coprecipitation reaction is 50~90℃, such as 50℃, 55℃, 60℃, 65℃, 70℃, 75℃, 80℃, 85℃, 90℃, etc. At these temperatures, it is advantageous to prepare secondary particles with high sphericity, suitable porosity, and uniform particle size.
[0079] According to some embodiments of the present invention, the coprecipitation reaction is carried out in a low-oxygen atmosphere or an inert atmosphere, and the volume ratio of oxygen in the reaction atmosphere is ≤5%, for example, it can be 0, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc. Therefore, under the above reaction atmosphere conditions, the morphology and growth of secondary particles can be better controlled, and the risk of side reactions can be reduced.
[0080] According to some embodiments of the present invention, the solid content in the co-precipitation reaction is 400-1000 g / L, for example, solid content of 400 g / L, 450 g / L, 500 g / L, 550 g / L, 600 g / L, 650 g / L, 700 g / L, 750 g / L, 800 g / L, 850 g / L, 900 g / L, 950 g / L, 1000 g / L, etc. The above-mentioned solid content is beneficial to the formation of secondary particles and helps to obtain secondary particles with better sphericity and particle size uniformity.
[0081] In some embodiments of the present invention, the particle size (e.g., D50) of the secondary particles obtained is monitored in real time during the co-precipitation reaction. When the particle size of the secondary particles reaches the target particle size, the feeding is stopped, and a mixed slurry is obtained. The resulting mixed slurry can then be added to a filter press washing device for washing and filtration. It is washed successively with dilute sodium hydroxide solution and pure water. After washing, it is sent to a drying process, and then sequentially sieved through a filter screen (e.g., 325 mesh) and demagnetized to obtain ternary cathode precursor material particles with a porosity gradient distributed radially from the inside out.
[0082] In another aspect, the present invention provides a ternary cathode material. According to an embodiment of the present invention, the ternary cathode material is prepared from a lithium source and the aforementioned ternary cathode material precursor particles. This ternary cathode material exhibits low internal impedance during long-cycle operation, and the electrolyte can rapidly penetrate and diffuse into the interior of the ternary cathode material particles, thereby contributing to improved battery cycle life and rate capability. Those skilled in the art will understand that this ternary cathode material possesses all the characteristics and advantages of the aforementioned ternary cathode material precursor particles, which will not be elaborated upon further here.
[0083] In some embodiments, the ternary cathode material can be obtained by high-temperature sintering of the lithium source and the aforementioned ternary cathode material precursor particles.
[0084] There are no specific requirements for the material of the lithium source. Those skilled in the art can make flexible choices according to actual needs. For example, lithium sources include, but are not limited to, lithium carbonate, lithium hydroxide, lithium nitrate, lithium acetate, lithium chloride, etc.
[0085] In another aspect, the present invention provides a battery. According to an embodiment of the present invention, the battery includes a positive electrode sheet, the positive electrode sheet including a positive current collector and a positive active film layer located on the surface of the positive current collector, the positive active film layer including the aforementioned ternary positive electrode material. Therefore, the battery has good cycle life, rate capability, and other battery performance.
[0086] In some embodiments, the positive electrode active film layer may include, in addition to the ternary positive electrode material, materials such as binders and conductive agents.
[0087] In some specific embodiments, the adhesive may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.
[0088] In some specific embodiments, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0089] In some specific embodiments, the positive current collector can be a metal foil, such as aluminum foil.
[0090] Of course, those skilled in the art will understand that, in addition to the aforementioned positive electrode, the battery also includes a negative electrode, electrolyte, separator, and other structures.
[0091] In some embodiments, the battery may be a lithium-ion battery.
[0092] Example Example 1 Step 1: Prepare the reaction solution Nickel sulfate, cobalt sulfate, manganese sulfate, and pure water were mixed in a nickel-cobalt-manganese mixed metal salt solution with a concentration of 134 g / L, prepared by a nickel-cobalt-manganese molar ratio of 97:1:2. The precipitant was a sodium hydroxide solution with a concentration of 320 g / L, and the complexing agent was an ammonia solution with a mass fraction of 9%. Step 2: Preparation of nickel-cobalt-manganese ternary cathode material precursor Preparation of the base solution: A reaction vessel with an effective volume of 500 L was selected as the reactor. 10 mL of the base solution was continuously introduced into the reactor at a flow rate of 100 L / min. 3 Nitrogen gas was used to replace the air in the reactor. At the same time, 320 L of pure water was added as the base liquid. An appropriate amount of ammonia solution was added to adjust the ammonia concentration of the base liquid to 9.0 g / L. Sodium hydroxide solution was added to adjust the pH value of the base liquid (at 45℃) to 11.40. Stirring was started at 330 rpm and the reaction temperature was maintained at 70℃. The process of co-precipitation reaction to grow secondary precursor particles: A mixed solution of nickel-cobalt-manganese metal salts, sodium hydroxide solution, and ammonia solution are added to the reactor and mixed with the bottom liquid to carry out the core-outer layer growth reaction. The synthesis time is 0-3 hours for core formation, followed by the growth of the outer layer of secondary particles after 3 hours. When the average particle size D50 of the secondary particles reaches 12 μm during the growth reaction, the feeding is stopped, and a mixed slurry is obtained. The requirements for each raw material and the pH value (at 45℃), stirring speed, and other parameters of the reaction system are shown in Table 1 below.
[0093] Table 1
[0094] The reason why the ammonia concentration gradually decreased from 9.0 g / L to 3.0 g / L in the table above is that metal salts and sodium hydroxide solutions were added, which reduced the ammonia concentration in the entire mixed solution.
[0095] Step 3: Post-processing The mixed slurry obtained in step 2 is added to a filter press washing equipment for washing and filtration. It is washed with dilute sodium hydroxide solution and pure water in sequence. After completion, it is sent to the drying process, and then sieved through a 325-mesh filter and demagnetized to obtain ternary cathode precursor material particles including a core and an outer layer. The porosity of the core is 8.62%, the porosity of the outer layer is 3.26%, and the ratio of the diameter of the core to the particle size D50 of the secondary particles is 0.24.
[0096] Scanning electron microscopy (SEM) was performed on the ternary precursor material particles and their cross-section obtained in Example 1. Figure 3 and Figure 4 As shown.
[0097] Example 2 Step 1: Prepare the reaction solution Nickel sulfate, cobalt sulfate, manganese sulfate, and pure water were mixed in a nickel-cobalt-manganese mixed metal salt solution with a concentration of 134 g / L, prepared by a nickel-cobalt-manganese molar ratio of 97:1:2. The precipitant was a sodium hydroxide solution with a concentration of 320 g / L, and the complexing agent was an ammonia solution with a mass fraction of 9%. Step 2: Preparation of nickel-cobalt-manganese ternary cathode material precursor Preparation of the base solution: A reaction vessel with an effective volume of 500 L was selected as the reactor. 10 mL of the base solution was continuously introduced into the reactor at a flow rate of 100 L / min. 3 Nitrogen gas was used to replace the air in the reactor. At the same time, 320 L of pure water was added as the base liquid. An appropriate amount of ammonia solution was added to adjust the ammonia concentration of the base liquid to 9.0 g / L. Sodium hydroxide solution was added to adjust the pH value of the base liquid (at 45℃) to 11.40. Stirring was started at 280 rpm and the reaction temperature was maintained at 70℃. The process of co-precipitation reaction to grow secondary precursor particles: A mixed nickel-cobalt-manganese metal salt solution, sodium hydroxide solution, and ammonia solution are added to a reactor to carry out a core-outer layer growth reaction. The synthesis time is 0-3 hours for core formation, followed by the growth of the outer layer of secondary particles after 3 hours. When the average particle size D50 of the secondary particles reaches 12 μm during the growth reaction, the feeding is stopped, and a mixed slurry is obtained. The requirements for each raw material and parameters of the reaction system, such as pH value (at 45℃) and stirring speed, are shown in Table 2 below.
[0098] Table 2
[0099] The reason why the ammonia concentration gradually decreased from 9.0 g / L to 5.0 g / L in the table above is that metal salts and sodium hydroxide solutions were added, which reduced the ammonia concentration in the entire mixed solution.
[0100] Step 3: Post-processing The mixed slurry obtained in step 2 is added to a filter press washing equipment for washing and filtration. It is washed with dilute sodium hydroxide solution and pure water in sequence. After completion, it is sent to the drying process, and then sieved through a 325-mesh filter and demagnetized to obtain ternary cathode precursor material particles including a core and an outer layer. The porosity of the core is 7.24%, the porosity of the outer layer is 2.68%, and the ratio of the diameter of the core to the particle size D50 of the secondary particles is 0.45.
[0101] Scanning electron microscopy (SEM) was performed on the ternary precursor material particles and their cross-sections obtained in Example 2. Figure 5 and Figure 6 As shown.
[0102] Example 3 The difference from Example 1 is that: at 16-18h, the alkali feed pump was turned off, and the pH was rapidly reduced to 11.4, while the other parameters remained unchanged. After 18h, the pH was 11.4.
[0103] Ternary cathode precursor material particles comprising a core and an outer layer were prepared. The porosity of the core was 8.64%, the porosity of the outer layer was 4.88%, and the ratio of the core diameter to the particle size D50 of the secondary particles was 0.19.
[0104] Example 4 The difference from Example 3 is that, during 16-18 hours, the ammonia concentration decreased uniformly to 2.6 g / L at a rate of 0.6 g / L·h, while the other parameters remained unchanged, and the ammonia value was 2.6 g / L after 18 hours.
[0105] Ternary cathode precursor material particles comprising a core and an outer layer were prepared. The porosity of the core was 8.74%, the porosity of the outer layer was 5.98%, and the ratio of the core diameter to the particle size D50 of the secondary particles was 0.52.
[0106] Example 5 The difference from Example 2 is that, from 0 to 3 hours, the flow rate of the metal salt solution was 5 L / h, and from 3 to 11 hours (a total of 8 hours), the flow rate was increased at a constant rate of 0.74 L / h to 10.92 L / h, while the other parameters remained unchanged. After 11 hours, the flow rate of the metal salt solution was 10.92 L / h.
[0107] Ternary cathode precursor material particles comprising a core and an outer layer were prepared. The porosity of the core was 7.14%, the porosity of the outer layer was 3.38%, and the ratio of the core diameter to the particle size D50 of the secondary particles was 0.49.
[0108] Comparative Example 1 Step 1: Prepare the reaction solution Nickel sulfate, cobalt sulfate, manganese sulfate, and pure water were mixed in a nickel-cobalt-manganese mixed metal salt solution with a concentration of 134 g / L, according to a nickel-cobalt-manganese molar ratio of 97:1:2. The precipitant was a sodium hydroxide solution with a concentration of 320 g / L, and the complexing agent was an ammonia solution with a mass fraction of 9%. Step 2: Preparation of nickel-cobalt-manganese ternary precursor seed crystals Preparation of the first base solution: A reactor with an effective volume of 500 L was selected as the first reaction vessel. 10 m³ of solution was continuously introduced into the first reaction vessel at a flow rate of 100 L / min. 3Nitrogen gas was used to replace the air in the reactor. At the same time, 220 L of pure water was added as the base liquid. An appropriate amount of ammonia solution was added to adjust the ammonia value of the base liquid to 4.8 g / L. Sodium hydroxide solution was added to adjust the pH value of the base liquid (at 45℃) to 11.95. Stirring was started at 400 rpm, and the reaction temperature was maintained at 70℃.
[0109] Core reaction process: A mixed nickel-cobalt-manganese metal salt solution, sodium hydroxide solution, and ammonia solution are introduced into the first reactor to carry out the core formation reaction; the flow rate of the mixed nickel-cobalt-manganese metal salt solution is 6 L / h throughout the entire core formation reaction process; First growth reaction process: The core reaction time is 1 hour. After the reaction is completed, the pH value is uniformly reduced to 10.80 (at 45°C) within 30 minutes. The flow rate of the nickel-cobalt-manganese mixed metal salt solution is increased to 25 L / h. During this period, the stirring speed is maintained at 400 rpm. Feeding was stopped when the average particle size D50 of the material in the first reactor reached 3.6 μm. The slurry was washed and dried and then used as seed crystals for later use. Step 3: Prepare nickel-cobalt-manganese cathode material precursor.
[0110] Preparation of the second base liquid: A reactor with an effective volume of 500 L was selected as the second reaction vessel. 10 m³ of solution was continuously introduced into the second reaction vessel at a flow rate of 100 L / min. 3 Nitrogen gas was used to replace the air in the reactor. At the same time, 320 L of pure water was added as the base liquid. An appropriate amount of ammonia solution was added to adjust the ammonia value of the base liquid to 6.0 g / L. Sodium hydroxide solution was added to adjust the pH value of the base liquid (at 45℃) to 10.90. Stirring was started at 400 rpm, and the reaction temperature was maintained at 70℃. The second growth reaction process: A mixed nickel-cobalt-manganese metal salt solution, sodium hydroxide solution, and ammonia solution are added to the second reaction vessel to initiate the second growth reaction. Feeding is stopped when the average particle size (D50) of the secondary particles reaches 12 μm during the second growth reaction, yielding a mixed slurry. The requirements for each raw material and the pH value (at 45℃), stirring speed, and other parameters of the reaction system are shown in Table 3 below.
[0111] Table 3
[0112] Step 4: Post-processing The mixed slurry obtained in step 2 is added to a filter press washing equipment for washing and filtration. It is washed with dilute sodium hydroxide solution and pure water in sequence. After completion, it is sent to the drying process, and then sieved through a 325-mesh filter and demagnetized to obtain ternary cathode precursor material particles.
[0113] Scanning electron microscopy (SEM) was performed on the ternary precursor material particles and their cross-sections obtained in Comparative Example 1. Figure 7 and Figure 8 As shown. (Through) Figure 7 It can be seen that the core of the ternary cathode precursor material particles is not obvious, that is, the diameter of the core is very small, and there is no obvious change in the porosity of the particles as a whole. Through testing, the porosity of the ternary cathode precursor material particles is 0.12.
[0114] Comparative Example 2 Step 1: Prepare the reaction solution Nickel sulfate, cobalt sulfate, manganese sulfate, and pure water were mixed in a nickel-cobalt-manganese mixed metal salt solution with a concentration of 134 g / L, according to a nickel-cobalt-manganese molar ratio of 97:1:2. The precipitant was a sodium hydroxide solution with a concentration of 320 g / L, and the complexing agent was an ammonia solution with a mass fraction of 9%. Step 2: Preparation of nickel-cobalt-manganese ternary precursor seed crystals Preparation of the first base solution: A reactor with an effective volume of 500 L was selected as the first reaction vessel. 10 m³ of solution was continuously introduced into the first reaction vessel at a flow rate of 100 L / min. 3 Nitrogen gas was used to replace the air in the reactor. At the same time, 220 L of pure water was added as the base liquid. An appropriate amount of ammonia solution was added to adjust the ammonia value of the base liquid to 2.5 g / L. Sodium hydroxide solution was added to adjust the pH value of the base liquid (at 45℃) to 11.75. Stirring was started at 400 rpm, and the reaction temperature was maintained at 65℃.
[0115] Core reaction process: A mixed nickel-cobalt-manganese metal salt solution, sodium hydroxide solution, and ammonia solution are introduced into the first reactor to carry out the core formation reaction; the flow rate of the mixed nickel-cobalt-manganese metal salt solution is 6 L / h throughout the entire core formation reaction process; First growth reaction process: The core reaction time is 1 hour. After the reaction is completed, the pH value is uniformly reduced to 10.65 (at 45°C) within 30 minutes. The flow rate of the nickel-cobalt-manganese mixed metal salt solution is increased to 18 L / h. During this period, the stirring speed is maintained at 400 rpm. Feeding was stopped when the average particle size D50 of the material in the first reactor reached 3.7 μm. The slurry was washed and dried and then used as seed crystals for later use. Step 3: Prepare nickel-cobalt-manganese cathode material precursor.
[0116] Preparation of the second base liquid: A reactor with an effective volume of 500 L was selected as the second reaction vessel. 10 m³ of solution was continuously introduced into the second reaction vessel at a flow rate of 100 L / min. 3Nitrogen gas was used to replace the air in the reactor. At the same time, 320 L of pure water was added as the base liquid. An appropriate amount of ammonia solution was added to adjust the ammonia value of the base liquid to 6.0 g / L. Sodium hydroxide solution was added to adjust the pH value of the base liquid (at 45℃) to 11.55. Stirring was started at 400 rpm, and the reaction temperature was maintained at 65℃. The second growth reaction process: A mixed nickel-cobalt-manganese metal salt solution, sodium hydroxide solution, and ammonia solution are added to the second reaction vessel to initiate the second growth reaction. Feeding is stopped when the average particle size D50 of the secondary particles reaches 12 μm during the second growth reaction, yielding a mixed slurry. The requirements for each raw material and the pH value (at 45℃), stirring speed, and other parameters of the reaction system are shown in Table 4 below.
[0117] Table 4
[0118] Step 4: Post-processing The mixed slurry obtained in step 2 was added to a filter press washing device for washing and filtration. It was washed successively with dilute sodium hydroxide solution and pure water. After washing, it was sent to a drying process, and then successively sieved through a 325-mesh filter and demagnetized to obtain ternary cathode precursor material particles. The core of these ternary cathode precursor material particles is not obvious, indicating that the diameter of the core is very small. The overall porosity of the particles does not show significant changes. Testing showed that the porosity of these ternary cathode precursor material particles is 0.13. Examples 1-1 to 5-1 and Comparative Examples 1-1 and 2-1 Batteries were prepared using the ternary cathode material precursor particles obtained in Examples 1-5 and Comparative Examples 1-2, as detailed below: 1. Preparation of ternary cathode materials The ternary cathode material precursor particles obtained in Examples 1-5 and Comparative Examples 1-2 were used to prepare corresponding ternary cathode materials. The steps included: taking the ternary cathode material precursor particles prepared in the above examples and comparative examples, placing them in a sintering furnace, and performing high-temperature sintering under inert gas protection. After sintering, the particles were crushed, graded, and sieved to obtain ternary cathode materials with uniform particle size. The inert gas was argon or nitrogen, the sintering temperature was 800-1000℃, the sintering time was 8-12h, and the grading and sieving were performed using a 200-300 mesh sieve.
[0119] 2. Preparation of positive electrode sheet The ternary cathode material, conductive agent carbon black, and binder polyvinylidene fluoride prepared above were weighed out in a mass ratio of 86:7:7 and added together to the solvent N-methylpyrrolidone. The mixture was stirred at high speed until homogeneous, yielding a cathode slurry with a solid content of 50 wt%. This cathode slurry was then uniformly coated onto the surface of an aluminum foil current collector to a thickness of 86 μm. The coated material was then placed in a vacuum drying oven and dried at 100°C for 6 hours to remove the solvent. After drying, the electrode was subjected to roller pressing, resulting in a compaction density of 2.2 g / cm³. 3 Then, the electrode is cut into a preset size using a die-cutting process to obtain the positive electrode sheet.
[0120] 3. Preparation of negative electrode sheet The negative electrode active material, conductive agent, and binder are weighed out according to a mass ratio of 90-95:2-5:2-5, dispersed in a solvent, and then stirred and ultrasonically dispersed to prepare a uniform negative electrode slurry. The negative electrode slurry is coated onto the surface of a copper foil current collector with a coating thickness of 85μm. After vacuum drying, rolling, and die-cutting, the negative electrode sheet is obtained. The negative electrode active material is graphite, the conductive agent is carbon black, the binder is a compound system of sodium carboxymethyl cellulose and styrene-butadiene rubber, and the solvent is deionized water.
[0121] 4. Battery assembly The prepared positive electrode, separator, and negative electrode are stacked or wound in the order of "positive electrode - separator - negative electrode" to form a battery core. The battery core is then installed into a battery casing, electrolyte is injected, and then it is encapsulated. After encapsulation, formation and aging processes are performed sequentially to obtain the finished 2032 coin cell battery. The separator is a polypropylene / polyethylene composite separator, the electrolyte is a mixture of lithium hexafluorophosphate and carbonate solvent, the formation temperature is 30°C, the formation time is 2 hours, the aging temperature is 50°C, and the aging time is 18 hours.
[0122] The electrical properties of the prepared batteries were tested, and the results are shown in Table 5. During the tests, the charge / discharge rate was 0.1C, the voltage window was 2.8V to 4.4V, the test temperature was 25 degrees Celsius, and the cycle capacity retention rate was calculated as the discharge capacity after 100 cycles divided by the discharge capacity after the first cycle. Each set of data in Table 5 represents the average value obtained from five parallel experiments.
[0123] Table 5
[0124] As shown in Table 5, in Examples 1-1 to 5-1, the battery capacity retention rate can reach over 90% after 100 cycles, and the battery capacity is over 220 mAh / g. Its performance is significantly better than Comparative Examples 1-1 and 2-1. This shows that the ternary cathode material precursor particles of this application can effectively reduce the internal impedance of the ternary cathode material during long-term cycling. Moreover, the high porosity core can also help the electrolyte to quickly penetrate and diffuse into the ternary cathode material particles, while buffering volume expansion and shortening the ion transport path. The low porosity outer layer can effectively ensure the stability of the ternary cathode material particle structure and energy density, thereby contributing to battery cycling.
[0125] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0126] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.
Claims
1. A ternary cathode material precursor particle, characterized in that, The ternary cathode material precursor particles are secondary particles formed by the agglomeration of primary particles. The ternary cathode material precursor particles include a core and an outer layer that surrounds the core. The porosity of the core is greater than that of the outer layer, and the ratio of the diameter of the core to the particle size D50 of the secondary particles is 0.1 to 1.
2. The ternary cathode material precursor particles according to claim 1, characterized in that, The ratio of the porosity of the core to the porosity of the outer layer is 1.5 to 4, and / or the ratio of the diameter of the core to the particle size D50 of the secondary particles is 0.1 to 0.
75.
3. The ternary cathode material precursor particles according to claim 2, characterized in that, The porosity of the core is greater than 7%, preferably, the porosity of the core is 7% to 30%; And / or, the maximum porosity of the outer layer is ≤7%.
4. The ternary cathode material precursor particles according to claim 2, characterized in that, The porosity of the outer layer near the core is greater than the porosity of the outer layer away from the core.
5. The ternary cathode material precursor particles according to claim 4, characterized in that, Along the direction from the outside to the inside, the outer layer includes at least two sub-outer layers, and the porosity of the sub-outer layers gradually decreases in the direction away from the core; Preferably, in the direction away from the core, the outer layer includes a first sub-outer layer and a second sub-outer layer disposed sequentially.
6. The ternary cathode material precursor particles according to claim 5, characterized in that, At least one of the following conditions must be met: The porosity of the first outer layer is 2%~4%; The porosity of the second outer sublayer is 1.1%~2.2%; The ratio of the thickness of the first sub-outer layer and the second sub-outer layer to the diameter of the secondary particle is 0.005~0.25, respectively; The thickness of the first sub-outer layer and the second sub-outer layer are each independently 0.3 to 1.5 μm.
7. The ternary cathode material precursor particles according to any one of claims 1 to 6, characterized in that, The diameter of the core is 1 to 10 micrometers, and / or the particle size D50 of the secondary particles is 6 to 30 μm.
8. The ternary cathode material precursor particles according to any one of claims 1 to 6, characterized in that, The secondary particles satisfy at least one of the following conditions: The tap density of the secondary particles is 1.85~2.15 g / cm³. 3 ; The sphericity of the secondary particles is 0.65~0.99; The specific surface area of the secondary particles is 3~30m². 2 / g; In the XRD test of the secondary particles, the peak intensity ratio I(001) / I(101) of the characteristic peak of the (001) crystal plane and the characteristic peak of the (101) crystal plane is 0.7~1.
2. The particle size distribution K90 of the secondary particles is 0.25~0.85, where K90=(D90-D10) / D50.
9. The ternary cathode material precursor particles according to any one of claims 1 to 6, characterized in that, The primary particle satisfies at least one of the following conditions: In the direction away from the core, the primary particles of the outer layer are arranged radially; The primary particle morphology includes at least one of the following: plate-like, rod-like, and block-like. Optionally, the average thickness of the sheet-like primary particles is 5-200 nm, preferably 80-170 nm; Optionally, the average length of the sheet-like primary particles is 200~450 nm; Optionally, the aspect ratio of the rod-shaped primary particles is 20 to 200.
10. A method for preparing ternary cathode material precursor particles according to any one of claims 1 to 9, characterized in that, include: The precipitant and complexing agent are mixed in a reaction vessel to prepare the base solution; In the first reaction stage, the precipitant, the complexing agent and the metal salt solution are continuously added to the base liquid to obtain a first-stage mixture and form the core of the ternary cathode material precursor particles, and then enter the second reaction stage. In the second reaction stage, the precipitant, the complexing agent, and the metal salt solution are continuously added to the mixture from the first stage to obtain the ternary cathode material precursor particles. In the first reaction stage, the flow rates of the precipitant, the complexing agent, and the metal salt solution are all less than those in the second reaction stage, and the pH value of the first reaction stage is greater than or equal to that of the second reaction stage, and the stirring speed of the first reaction stage is greater than that of the second reaction stage.
11. The method according to claim 10, characterized in that, In the first reaction stage, the flow rate A1 of the metal salt solution, the flow rate B1 of the complexing agent, and the flow rate C1 of the precipitant remain unchanged, and the concentration D1, pH value E1, and stirring speed F1 of the complexing agent remain unchanged.
12. The method according to claim 11, characterized in that, The second reaction stage satisfies at least one of the following conditions: The flow rate of the added metal salt solution gradually increases from A1 to A2 within a first predetermined time and then remains constant. The addition flow rate of the complexing agent is gradually increased from B1 to B2 within the first predetermined time period, and remains unchanged at B2 within the second predetermined time period. Then, B2 is gradually decreased to B3 within the third predetermined time period and remains unchanged thereafter, with B2>B3>B1. The flow rate of the precipitant is gradually increased from C1 to C2 within the first predetermined time period, and remains constant at C2 within the second predetermined time period. Then, C2 is gradually decreased to C3 within the third predetermined time period and remains constant thereafter, with C2>C3>C1. The concentration of the complexing agent is gradually increased from D1 to D2 within the first predetermined time period, and remains unchanged at D2 within the second predetermined time period. Then, D2 is gradually decreased to D3 within the third predetermined time period and remains unchanged thereafter, with D2>D3>D1. The pH value gradually decreases from E1 to E2 within the first predetermined time period, remains unchanged at E2 within the second predetermined time period, and then gradually decreases from E2 to E3 within the third predetermined time period and remains unchanged; or, the pH value remains unchanged at E1 within the fourth predetermined time period, and then gradually decreases from E1 to E2 and remains unchanged. The stirring speed is gradually reduced from F1 to F2, maintained at F2 for a certain period of time, then gradually reduced from F2 to F3, maintained at F3 for a certain period of time, then gradually reduced from F3 to F4, and so on, gradually reduced from Fn-1 to Fn and then kept constant, where n is an integer greater than or equal to 3.
13. The method according to claim 12, characterized in that, The second reaction stage satisfies at least one of the following conditions: A1 is 3~16L / h, A2 is 18~35L / h, and the flow rate is increased at a constant rate of 1~3.5L / h during the process of gradually increasing from A1 to A2. B1 is 0.5~10L / h, B2 is 3~20L / h, and B3 is 2~15L / h. As B1 gradually increases to B2, the flow rate is increased at a constant rate of 0.1~1.2L / h. As B2 gradually decreases to B3, the flow rate is decreased at a constant rate of 0.1~1.5L / h. C1 is 3.5~15L / h, C2 is 10~25L / h, and C3 is 6~20L / h. As C1 gradually increases to C2, the flow rate is increased at a constant rate of 0.5~2.5L / h. As C2 gradually decreases to C3, the flow rate is decreased at a constant rate of 0.2~1L / h. D1 is 0.5~10 g / L, D2 is 1.5~15 g / L, and D3 is 1~12 g / L. As D1 gradually increases to D2, the flow rate is increased at a constant rate of 0.05~0.3 g / L·h. As D2 gradually decreases to D3, the flow rate is decreased at a constant rate of 0.1~0.8 g / L·h. E1 is 11.8~12.5, E2 is 11.2~12.0, E3 is 10.3~11.2, and the rate of change of the pH value is 0.002 / h~0.3 / h; F1 is 50~500 rpm, and the rate of decrease of the stirring speed is 5~15 rpm / h.
14. The method according to any one of claims 10 to 13, characterized in that, The base fluid satisfies at least one of the following conditions: pH range: 10.45~11.95; The concentration of the complexing agent is 7.0~12 g / L.
15. The method according to any one of claims 10 to 13, characterized in that, At least one of the following conditions must be met: The concentration of the metal salt solution is 120~145 g / L. During the co-precipitation reaction, the flow rate of the metal salt solution added is 1.0%~10.0% of the available volume of the reaction vessel. The complexing agent has a mass fraction of 7-10 wt%, and during the coprecipitation reaction, the flow rate of the complexing agent is 0.3%-3% of the available volume of the reaction vessel. The concentration of the precipitant is 200~450 g / L, and during the coprecipitation reaction, the flow rate of the precipitant is 1.5%~10% of the usable volume of the reaction vessel.
16. The method according to claim 15, characterized in that, At least one of the following conditions must be met: The reaction temperature for the coprecipitation reaction is 50~90℃; The coprecipitation reaction is carried out in a low-oxygen atmosphere or an inert atmosphere, and the volume proportion of oxygen in the reaction atmosphere is ≤5%; The solid content in the coprecipitation reaction is 400-1000 g / L.
17. A ternary cathode material, characterized in that, It is prepared from a lithium source and ternary cathode material precursor particles according to any one of claims 1 to 9.
18. A battery, characterized in that, The positive electrode includes a positive current collector and a positive active film layer located on the surface of the positive current collector, wherein the positive active film layer includes the ternary positive electrode material as described in claim 17.